STUDY OF THE VARROASIS INFESTATION RATE IN THE CENTRAL AREA OF ECUADOR - SILVA, VINICIO MONTALVO; CLAVIJO, FABIAN MONTES; VILLAFUERTE, GUILLERMO; RUIZ, DOLORES ORTEGA; JACOME, VICENTE; SANCHEZ, MANUEL DUVERLI; VELASCO, KLEVER (International Journal of Current Pharmaceutical Research, 2020)
Objective: To study the Varroasis Infestation rate in the central area of Ecuador. Methods: The experimental phase was developed in four apiaries distributed in the provinces: Bolivar, Tungurahua, Chimborazo and Los Rios (12 hives), the experimentation lasted 65 d. A DCA design was applied. Three different systems were used for the identification of varroa: soapy water (SW), honeycomb cut (HC) and the cardboard with semi-solid petrolatum (CSP). Results: With the SW method, it was obtained that Chimborazo has 23.14%; followed by Tungurahua (7.99%); Los Rios (3.24%) and finally Bolivar with (0.51%); with the HC method, it was determined that Chimborazo has the highest incidence with 9.13%; followed by Bolivar and finally Los Rios; with the CSP method, the province of Chimborazo presents the highest infestation (26250 individuals); followed by Bolivar, Tungurahua, and Los Rios. Regarding the production of eggs for each frame, 3 frames taken from the brood chamber were used in each of the apiaries under study; Chimborazo being where there is less quantity of eggs for each frame, followed by Bolivar, Tungurahua and finally Los Ríos. Conclusion: The higher the geographical height, the greater the Varroa infestation.